Peran Nilai Tri Kaya Parisudha dalam Membentuk Profesionalisme Jurnalis Hindu di Zaman Modern - I Kadek Agus Yadnya (Dharma Duta, 2026)
This article examines Tri Kaya Parisudha as an internal ethical framework for strengthening the professionalism of Hindu journalists in the digital media era. Using a literature review approach, the study analyzes academic works on digital journalism, misinformation, algorithmic bias, fact-checking, and Hindu ethical values, then maps them into the three dimensions of manacika, wacika, and kayika. The analysis shows that manacika functions as cognitive discipline in resisting premature publication and prioritizing verification; wacika functions as language ethics that guide accurate, proportional, and socially responsible reporting; and kayika functions as concrete professional action expressed in verification routines, editorial independence, and openness to correction. The study argues that Tri Kaya Parisudha does not merely represent a moral doctrine, but can be formulated as an operational ethical framework relevant to contemporary journalism. Its contribution lies in connecting Hindu ethical values with the challenges of digital journalism, particularly misinformation, speed pressure, and polarized information environments. However, its implementation requires support from newsroom governance and ethics-based journalistic education